A Powerful Influence: An Online Book Club for Educators. Issue 2 (3rd April 2018) - Porath, Suzanne L.
Abstract: Opportunities for self-directed and connected professional learning are made possible by applications and tools available on the Internet and are part of an educator's professional learning network (PLN). For the past 6 years, educators across the world have reflected together through a voluntary, educator-generated, informal, online professional book club conducted through a variety of platforms including blogs, Twitter, and Google+. Using a survey and interviews, this study examined the self-reported participation and perceived learning of 26 participants in the affinity space known as the #CyberPD community during the summer of 2015. The educators who participated in the book club engaged in responding to the book through a variety of platforms, valued the diversity of perspectives represented, highlighted the importance of applying their learning to their classrooms, and appreciated the connections they made with supportive colleagues. Teacher educators and school districts are encouraged to consider how they are supporting educators in developing and sustaining useful PLNs for professional learning that is flexible, relevant, and connective. (Keywords: professional development, professional learning network, affinity space, book club, teacher learning)